Apolipoprotein E polymorphism carriers exhibit objective cognitive deficits: a single center trial. (2nd August 2020) - Zeng, Yanfang; Huang, Xin; Elkin, Kenneth; Stone, Christopher; Rajah, Gary B.; Guan, Longfei; Du, Huishan; Geng, Xiaokun
ABSTRACT: Objective: To assess the correlation between objectively measured cognitive function and apolipoprotein E polymorphism within one geographic region. Methods: 61 patients, aged 55–90 years old, were enrolled in a memory clinic at the Beijing Luhe Hospital affiliated with Capital Medical University from September 2016 to September 2018. At this center, they were evaluated with neuropsychological scales to assess their memory and other aspects of cognitive function. Specific gene segments were extracted from venous blood by PCR amplification, and ApoE genotyping was carried out by chip hybridization. Results: Among all patients, 0 had the genotype ε2/2, 7 had the genotype ε2/3, 0 had the genotype ε2/4, 40 had the genotype ε3/3, 12 had the genotype ε3/4, and 2 had the genotype ε4/4. The allele frequency ε2 accounted for 5.74%, ε3 accounted for 81.15% and ε4 accounted for 13.11%. The Mini-Mental State Examination (MMSE) scores of ε4 carriers (18.14 ± 0.39) were significantly lower than those of non-ε4 carriers (23.77 ± 6.29) (P < 0.05), and the Montreal Cognitive Assessment (MoCA) scores of ε4 carriers (14.36 ± 7.56) were also significantly lower than those of non-ε4 carriers (20.55 ± 8.08) (P < 0.05). Conclusion: The rate of the ε3/3 homozygous genotype was the highest, followed by the rates of the ε3/4 and ε2/3 genotypes. The rates of the ε2/4, ε4/4, and ε2/2 genotypes were the lowest. Deficits in memory and other cognitive processes were significantly more pronounced in ε4 carriers than in non-ε4 carriers.